Outcomes of the hexapod frame in 111 ‘high risk’ tibial fractures - Jonathan France; Adam Tucker; Jessica Nightingale; Andrew Taylor; Simon Craxford; Benjamin Ollivere (Bone & Joint Open)
Aims: The use of circular frames in the management of tibia fractures and deformity correction is well established in the literature. The Taylor Spatial Frame (TSF) is the most widely used hexapod device globally. However, the majority of published papers are small in patient numbers, contain primary and revision cases, and outcomes are therefore unclear. In this study we evaluate the clinical and radiological outcomes of patients with tibial fractures treated primarily with a TSF. Methods: Patients were identified from a prospective trauma database at a UK major trauma centre. An analysis of patient records and radiographs was performed for the study. Patient demographics, comorbidities, frame construct, time in frame, union rates, and complications of treatment were analyzed. Results: Between September 2009 and January 2020, 111 patients with tibial fractures managed primarily with a TSF were included. The majority of patients (86, 77.5%) sustained fractures to the tibial shaft, leaving nine plateau (8.1%) and 16 pilon fractures (14.4%). Of these, 55 (49.6%) were open and 56 (50.4%) were closed. Of the open fractures, seven were classified as Gustilo and Anderson grade 3A and 41 (74.5%) were classified as grade 3B. The overall union rate for primary TSF was 85%, with a mean time to union of 191 days (SD 90). A total of 15 patients (13.5%) required either open reduction and internal fixation (n = 6, 5.4%) or intramedullary nail (n = 9, 8.2%) to achieve bony union. Five patients (4.5%) developed a deep infection requiring invasive treatment. Two patients (1.8%) required an eventual amputation for an infected nonunion; both of these patients sustained an initially closed fracture. Overall limb salvage at two years was 98.2%. Conclusion: The TSF remains an established option in the surgical management of patients with complex injuries to the tibia, with good rates of limb salvage within this challenging patient subgroup. Cite this article: Bone Jt Open 2025;6(7):816–821.